2014
DOI: 10.1088/1674-1056/23/1/013601
|View full text |Cite
|
Sign up to set email alerts
|

Structure, stability and electronic properties of SrSi n ( n = 1–12) clusters: Density-functional theory investigation

Abstract: Geometric structures, stabilities, and electronic properties of SrSi n (n = 1-12) clusters have been investigated using the density-functional theory within the generalized gradient approximation. The optimized geometries indicate that one Si atom capped on SrSi n−1 structure and Sr atom capped Si n structure for difference SrSi n clusters in size are two dominant growth patterns. The calculated average binding energy, fragmentation energy, second-order energy difference, the highest occupied molecular orbital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…[13] It is found that their physical and chemical properties depend on the size, structure, and chemical ordering of their components. [14][15][16][17][18][19] Scholl, [20] Lee et al, [21] Noguez, [22] Dong et al, [23] Gong et al, [24] and Guidez et al [25] revealed that the optical properties of metal clusters depend on their sizes, shapes, metal compositions, and surrounding environments. Baishya et al [26] indicated that more than one isomer of Ag clusters can contribute to the measured spectrum at specific sizes.…”
Section: Introductionmentioning
confidence: 99%
“…[13] It is found that their physical and chemical properties depend on the size, structure, and chemical ordering of their components. [14][15][16][17][18][19] Scholl, [20] Lee et al, [21] Noguez, [22] Dong et al, [23] Gong et al, [24] and Guidez et al [25] revealed that the optical properties of metal clusters depend on their sizes, shapes, metal compositions, and surrounding environments. Baishya et al [26] indicated that more than one isomer of Ag clusters can contribute to the measured spectrum at specific sizes.…”
Section: Introductionmentioning
confidence: 99%
“…By examining the electrostatic potential energy maps, one can gain insights into the distribution of charge and the strength of chemical interactions within the clusters [12]. This information can then be used to assess the stability of the clusters and predict their reactivity [13].…”
Section: Introductionmentioning
confidence: 99%